Degradation behaviors of Isopropylphenazone and Aminopyrine and their genetic toxicity variations during UV/chloramine treatment. (1st March 2020) - Jiang, Bingqi; Tian, Yajun; Zhang, Zichen; Yin, Ze; Feng, Li; Liu, Yongze; Zhang, Liqiu
Abstract: Combination of ultraviolet and chloramine (i.e., UV/chloramine) treatment has been attracting increasingly attention in recent years due to its high efficiency in removing trace organic contaminants. This study investigated the degradation behaviors of two pyrazolone pharmaceuticals (i.e., Isopropyl phenazone (PRP) and Aminopyrine (AMP)) and their genetic toxicity variations during UV/chloramine treatment. The results showed that chloramine could hardly degrade PRP and AMP, while UV/chloramine greatly increased the observed first-order rate constant ( k obs ) of PRP and AMP degradation. The quenching and probe experiments illustrated that the reactive chlorine species (RCS) contributed dominantly to PRP removal, and hydroxyl radical (HO ) was the major contributor to the degradation of AMP, while the reactive amine radicals (RNS) could hardly degrade them. The overall degradation rates of PRP and AMP decreased as pH increased from 6.5 to 10. The k obs of PRP and AMP increased along with NH2 Cl dosage increasing and reached a plateau at higher concentrations (0.2–0.5 mM). The present background carbonate (HCO3 −, 1–10 mM), chloride (Cl −, 1–10 mM) and natural organic matter (NOM, 5-10 mg-C L −1 ) exhibited inhibition impacts on PRP and AMP degradation. In addition, the intermediates/products of PRP and AMP were identified and their general degradation pathways were proposed to be hydroxylation, deacetylation, and dephenylization. Specifically, Cl-substitution was inferred during PRP degradation, while demethylation in tertiary amine group was only observed in AMP degradation. These mechanisms including the main reactive sites of PRP and AMP were further confirmed by the frontier orbitals calculation. Moreover, the results of the genetic toxicity according to the micronucleus test of Viciafaba root tip indicated that UV/chloramine treatment could partially reduce the genetic toxicity of PRP and AMP. Graphical abstract: Image 1 Highlights: UV significantly enhanced the oxidation of chloramine to decompose PRP and AMP. PRP degradation depended on RCS oxidation while AMP relied on HO. oxidation. Compared with PRP, AMP was more susceptible to HO. oxidation via DFT calculation. UV/chloramine treatment can partially reduce the genetic toxicity of PRP and AMP.